A REVISION OF JASMINUM (OLEACEAE) IN PENINSULAR MALAYSIA AND SINGAPORE, WITH CONSERVATION ASSESSMENTS. (29th November 2020) - Kiew, R.; Tan, J. P. C.
Abstract : The species of Jasminum Tourn. ex L. (Oleaceae) in Peninsular Malaysia are revised. Eighteen species are recognised, of which eight are endemic. Five of these species have been recorded from Singapore. A key to species is provided, all names are typified, and all species are described. Conservation assessments are given for all species in Peninsular Malaysia. One species is Extinct in Peninsular Malaysia, eleven are Endangered and one is Data Deficient. Jasminum shahii Kiew is described as a new species. In Singapore, two species are certainly Extinct.